In–out asymmetry and interference effects in plasmon excitation by swift charged particles traversing a surface. (17th October 2013) - Gervasoni, J. L.; Barrachina, R. O.; Segui, S.; Werner, W.
Abstract : We investigate the excitation of plasmons by a fast charged particle moving in the vicinity or traversing the surface of a solid along an arbitrary trajectory. We use both quantum‐mechanical and semiclassical dielectric formulations to study how the particle couples with the bulk and surface excitations. We pay special attention to the differences and similarities between incoming and outgoing trajectories, finding some novel oscillatory structures that can be ascribed to an interference effect between direct and reflected plasmon excitations. Copyright © 2013 John Wiley & Sons, Ltd.